2007
DOI: 10.1159/000103258
|View full text |Cite
|
Sign up to set email alerts
|

The Economo-Koskinas Atlas Revisited: Cytoarchitectonics and Functional Context

Abstract: The monumental Atlas of Cytoarchitectonics of the Adult Human Cerebral Cortex of Economo and Koskinas represents a gigantic intellectual and technical effort, never sufficiently recognized. One reason might have been the limited number of copies produced; another, the complex (albeit logical and precise) symbol notation, which comprises a Roman capital (from the initial of the respective lobe), a calligraphic capital (the sequence of a gyrus within a lobe), and a Latin or Greek subscript (for microscopic featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 48 publications
1
51
0
3
Order By: Relevance
“…The primary of these is the relatively low spatial resolution of the acquired MWF and T 1 images, (1.7 × 1.7 × 1.7) mm 3 , which may introduce partial volume effects that vary depending on child age and cortical region. This is particularly true in regions such as the primary somatosensory and visual cortex, which even in adults may be less than 2 mm thick (Triarhou, 2007). In these regions, the estimated MWF or T 1 value may be under or over-estimated, depending on whether the region contains CSF of white matter voxel averaging.…”
Section: Discussionmentioning
confidence: 99%
“…The primary of these is the relatively low spatial resolution of the acquired MWF and T 1 images, (1.7 × 1.7 × 1.7) mm 3 , which may introduce partial volume effects that vary depending on child age and cortical region. This is particularly true in regions such as the primary somatosensory and visual cortex, which even in adults may be less than 2 mm thick (Triarhou, 2007). In these regions, the estimated MWF or T 1 value may be under or over-estimated, depending on whether the region contains CSF of white matter voxel averaging.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of a "koniocortex core" and "prokoniocortex belt areas" in the temporal operculum (Pandya & Sanides, 1973) was modified by Kaas & Hackett (1998, 2000, who speak of histologically and functionally distinct "core", "belt" and "parabelt" subdivisions in the monkey auditory cortex, with specified connections. There are three major advantages in using the system of cytoarchitectonic areas defined by von Economo and Koskinas as opposed to the maps defined by Brodmann (von Economo, 2009;Triarhou, 2007aTriarhou, , 2007b: Koskinas (1885Koskinas ( -1975 to the Athens Medical Society 13 (Koskinas, 1931(Koskinas, , 2009 Koskinas, 2008) and in a related review (Triarhou, 2007b).…”
Section: Resultsmentioning
confidence: 99%
“…A tribute to his volume of work on cerebral cytoarchitectonics can be found in the recent release of his work. 9 Aviation When Constantin von Economo was not busy with histological studies, sleep theories, pathologoanatomic correlations and evolutionary studies, he found refuge in the skies. Fascinated by aeronautics he started in his early 30s to take balloon trips while in Paris; he obtained a In 1912 he obtained the first Austrian aeroplane pilot's licence.…”
Section: Cytoarchitecture Of the Human Cerebral Cortexmentioning
confidence: 99%